Preliminary Qualitative Analysis of Plant Samples by High-performance Thin-layer Chromatography for the Presence of Steroid Sapogenins of Some Representatives of the Dioscoreacae, Fabaceae, Ranunculaceae, Melanthiaceae, Scrophulariaceae - A. E. Sukhanov; I. A. Krylov; V. V. Sepp; K. S. Bakulin (Разработка и регистрация лекарственных средств, 2024)
Introduction. Results of original research carried out by means of high performance thin layer chromatography (HPTLC) of various plant samples (air-dry raw material) of Dioscoreaceae, Ranunculaceae, Fabaceae, Melanthiaceae, Scrophulariaceae families are presented in this article.Aim. To carry out preliminary qualitative analysis by HPTLC method of steroidal sapogenins composition in hydrolyzed extracts, obtained from vegetative samples of above-ground and underground organs of some Dioscoreaceae, Ranunculaceae, Fabaceae, Melanthiaceae, Scrophulariaceae families.Materials and methods. Extraction from pre-dehydrated raw materials was carried out with 50 % aqueous isopropanol (c.p.) in an ultrasonic bath, followed by acidic hydrolysis of O-glycoside bonds, evaporation and redissolution of dry residue in 99 % methanol (c.p.); purification from suspended solids by filtering through filters with 20 µm perforation diameter. HPTLC was performed on apparatus complex CAMAG (Switzerland) using HPTLC Aluminium sheets Silica gel 60 F254 plates 20 × 20 cm, which were cut to the size 20 × 10 cm.Results and discussion. After scanning densitometry at 254 nm, we found that the separation of isopropanol extracts, followed by redissolution in strong methanol in this solvent system allows a fairly acceptable separation and identification of the compounds studied. Comparison of the tracks of plant extracts was performed with standard samples of steroid sapogenins, whose methanol solutions were applied to one stain-strobe of track 1, provided that they had different Rf indices and coloration after derivatization.Conclusion. Diosgenin was identified in plant extracts of rhizomes and roots of Dioscorea nipponica and Dioscorea caucasica and in seeds of Trigonella foenum-graecum preliminarily. Sarsasapogenin was verified in extracts of fruits of Sophora japonica, tigogenin in extracts of seeds of Trigonella foenum-graecum, herb of Pulsatilla patens and herb of Veronica officinalis. Yamogenin was detected in extracts of seeds of Trigonella foenum-graecum and herb of Veronica officinalis. This work is exploratory in nature, assessing the presence of certain saponins by their sapogenins in selected extracts. We will optimize the HPLC separation procedure and choose other detection methods to unambiguously assess the co-presence of the studied sapogenins with approximately the same staining shades after derivatization and matching retention indices: there are pairs of steroidal sapogenins that have the same retention, we decided to group them in mixtures so that there would be separation within the group and subsequent comparison with the original extracts would make it possible to identify those or other sapogenins in such extracts.